The Economic Life Before Islam (Bahrain as a Model) (Journal of the College of Basic Education, 2025)
The Bahrain region is one of the important areas for internal and external trade in the Arabian Gulf, due to its connection through several important routes with the regions of the Arabian Peninsula and, via the sea, with countries around the world, especially India and China. The people of Bahrain were able to amass large amounts of wealth through their trade practices. This research focuses on Bahrain's geographical and commercial location and its impact on the economic life, which included agriculture, trade, and the pearl trade.The research is divided into three chapters:The first chapter covers the naming of Bahrain, its location, and the routes leading to it.The second chapter discusses the most important islands of Bahrain, such as Al-Ahsa, Al-Qatif, Al-Zarah, Jawatha, Darin, and other significant islands, and how some of them were opened up.The third chapter examines Bahrain's economic life, including agriculture, industry, internal and external trade, as well as fishing, which played an important role in the lives of the people of Bahrain, as they fished for pearls, a valuable commodity for them.